Scientific data, ecological conversion and transformative affect - Howell, Nancy (HTS teologiese studies, 2021)
Scientific data supporting rational arguments for human-made causes of climate and environmental changes might be persuasive in some contexts. Law, policy, activism and The Earth Charter similarly appear insufficient to change attitudes and behaviours. Even biblical and theological arguments fail to move some Christians beyond apathy and climate denial. Decades of ecological theology and calls for ecological conversion suggest that appeals to reason and facts are limited without an affective epistemology that join knowledge and experience to produce worldview transformation through emotions, such as awe.Contribution: Departing from appeal to scientific data and arguments alone, the primary claim is that ecological conversion is not singularly a rational act. For broader engagement and action to mitigate climate and environmental degradation, experiential and affective encounter with nature promise wider participation and transformation.